Utilization of Cashew Nut Waste as Cashew Nut Milk in Tanjungsari Village, Jatisrono Wonogiri: Pemanfaatan Limbah Kacang Mete sebagai Susu Kacang Mete di Desa Tanjungsari, Jatisrono Wonogiri - Novianto, Maulana Machfud Novianto; Mustofa, Akhmad (Fakultas Teknologi dan Industri Pangan Unisri Surakarta, 2025)
Tanjungsari village is one of the high cashew nut producing villages in Wonogiri district. The purpose of this service is to train mothers to utilize cashew nut waste into cashew nut milk. The method used in the service is direct training by including PKK mothers to participate in making cashew nut milk. The results showed that the PKK women were very excited to make cashew milk and were actively involved in the training process. The benefits of cashew nut milk are very good for children, pregnant women and also nursing mothers.